Atendimento educacional especializado: um estudo de caso de uma aluna com deficiência auditiva no município de Barcarena- PA - OLIVEIRA, Fryda Vingren Jaster de (2022)
This article deals with the challenge that the deaf face at school in order to be included in the teaching-learning process in a regular class at a school in the municipality of Barcarena-Pará. The objective of this study is to develop an AEE plan, through the teaching of Libras, that can meet the student's learning needs. As a method of analysis, we assumed a case study, which, for its development, resorted to an interview with the student's parents and with the student herself. It is expected with this study, to understand the difficulties of a deaf student in the classroom, based on Bogdan and Biklen (1994); Fonseca (2002), among others. However, based on the data, we found that the teaching of Libra should not only be available to the deaf student, but also from the teacher to the classroom teacher, since the student does not always have a Libras interpreter to support them. it in the understanding of the classes, moreover, this means that the schools that propose to the inclusion need the accompaniment of specialized people for the communication of these deaf students, to facilitate their learning effectively.